الجملة الاسمية في سورة النور من القرآن الكريم و معانيها - MUHAMMAD NUR HIDAYAT; AHMAD SEHRI BIN PUNAWAN (Albariq: Jurnal Pendidikan Bahasa Arab, 2021)
The research aims to analyse jumlah ismiyah or mubtada’ khabar in surah An Nur. The research focuses at which ayah was contained jumlah ismiyah or mubtada khabar, and how was I’rab, meanings, and tafsir of ayat at surah An Nur. The research is literature review. The result shows there was 48 ayat contained Jumlah Ismiyah or Mubtada’ Khabar.